Amiodarone Induced Morphological Changes in Rabbit Pneumocytes - Fereshteh Mehraein; Alireza Shams (Cell Journal, 2009)
Objective: Amiodarone as an iodinated benzofuran derivative is a potent antiarrhythmicagent currently used for the treatment of ventricular arrhythmias. Pulmonary toxicityis one of the complications of Amiodarone therapy. The aim of this study was todetermine the toxicity of Amiodarone for pneumocytes.Materials and Methods: 14 male white New Zealand rabbits were divided in a controlgroup and an experimental group. The experimental group was subjected to intraperitoneal injection with a single daily dose of 80 mg/kg Amiodarone for two weeks.The control group received only normal saline. At the end of the injection period, thetwo groups were anesthetized and perfused with Karnovsky fixative. The lung tissuewas removed and fixed, then prepared for light and electron microscope studies.Morphometric studies were made on sections to find nucleus profile dimensions.Results: Light microscope observation showed acute changes in the alveolus includingcongestion of alveolar capillaries and infiltration of red blood cells (RBCs) intothe lumen of the alveoli. Electron microscope study of lung tissue revealed abnormalinclusion bodies within type ΙΙ & Ι pneumocytes. The micrographs also showedthe presence of vacuoles in 5% of the type ΙΙ pneumocytes. Morphometric studiesshowed that the nucleus of the cells in the experimental group were smaller than inthe control group (p<0.01).Conclusion: These results indicate that Amiodarone administration can cause damageto pnuemocytes and the alveolus of rabbit lung, so the effectiveness of Amiodaronein long term treatment of heart failure patients is limited because of the developmentof lung toxicity.